Mothers' job search after childbirth - Lukás Lafférs; Bernhard Schmidpeter (Johannes Kepler University of Linz, Department of Economics, 2021)
We explore the impact of successful job search after childbirth on mothers' labor market careers. Using a bounding approach and administrative data, we find strong heterogeneity in the returns to leaving the pre-birth employer. Moving to a new employer after childbirth leads to an increase in re-employment earnings only for mothers at the upper part of the earnings distribution. For these mothers, initial job search also increases long-term earnings. We provide evidence that earnings gains are the result of higher geographical mobility and longer commutes to work. Successful mothers are also more likely to move to faster growing firms and firms offering better opportunities to women. Our results do not suggest that husbands play an important role in supporting successful job search of mothers.
Keywords: C21; J13; J31; J62; 330; parental leave; return-to-work; job search; earnings; earnings gaps